Rehabilitation of Atrophic Maxilla Using the Combination of Autogenous and Allogeneic Bone Grafts Followed by Protocol-Type Prosthesis - Margonar, Rogerio; dos Santos, Pamela Leticia [UNESP]; Queiroz, Thallita Pereira [UNESP]; Marcantonio, Elcio [UNESP] (Lippincott Williams & Wilkins, 2010)
Currently, there are several techniques for the rehabilitation of atrophic maxillary ridges in literature. The grafting procedure using autogenous bone is considered ideal by many researchers, as it shows osteogenic capability and causes no antigenic reaction. However, this type of bone graft has some shortcomings, mainly the restricted availability of donor sites. In recent years, several alternatives have been investigated to supply the disadvantages of autogenous bone grafts. In such studies, allogeneic bone grafts, which are obtained from individuals with different genetic load, but from the same species, have been extensively used. They can be indicated in cases of arthroplasty, surgical knee reconstruction, large bone defects, and in oral and maxillofacial reconstruction. Besides showing great applicability and biocompatibility, this type of bone is available in unlimited quantities. on the other hand, allogeneic bone may have the disadvantage of transmitting infectious diseases. Atrophic maxillae can be treated with bone grafts followed by osseointegrated implants to obtain aesthetic and functional oral rehabilitation. This study aimed to show the viability of allogeneic bone grafting in an atrophic maxilla, followed by oral rehabilitation with dental implant and protocol-type prosthesis within a 3-year follow-up period by means of a clinical case report.
Keywords: Homologous; bone transplantation; dental implantation